PENGARUH RETURN ON EQUITY (ROE) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PT ADI SARANA ARMADA Tbk PERIODE 2013-2022 - Dwi Novianti Salam, Nabilla; Bodewyn Mangasa Tua, Rudy (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Return On Equity (ROE) and Earning Per Share (EPS) on stock prices at PT Adi Sarana Armada Tbk for the period 2013-2022. The method used in this research is quantitative. And the methods used to analyze in this study include: Classical Assumption Test (Normality, Multicollinearity, Heteroscedasticity, and auto correlation) Multiple Linear Regression Test, Determination Coefficient Test, t Test (Partial) and F Test (Simultaneous). The results of this study indicate that Return On Equity (ROE) partially has a negative effect on stock prices by obtaining a tcount value of -4.008 > ttable 2.365 with a significance value of 0.005 < 0.05. Earning Per Share (EPS) partially has an influence on stock prices by obtaining a tcount value of 4,836> ttable 2,365 with a significance value of 0.002 <0.05. Simultaneously Return On Equity (ROE) and Earning Per Share (EPS) have an effect on stock prices by obtaining an fcount value of 11,772 > ftabel 4,737 and a significance value of 0.006 <0.05.